2002
DOI: 10.1074/jbc.m200148200
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific Effects of Fibulin-5 (DANCE/EVEC) on Cell Proliferation, Motility, and Invasion

Abstract: The Fibulin gene family comprises five distinct genes that encode more than eight protein products via alternative splicing. Fibulins are widely expressed secretory proteins found in the blood and in the basement membranes and stroma of most tissues, where they self-associate (e.g. Fibulins 1 and 2) (1, 2) and/or interact with a variety of extracellular matrix components, including fibronectin, laminin, nidogen, aggrecan, versican, endostatin, and elastin (3-5). Thus, Fibulins likely participate in the assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 39 publications
5
100
0
Order By: Relevance
“…The resulting PCR fragment was ligated into pcDNA3.1/Myc-His B vector (Invitrogen, Carlsbad, CA) at HindIII (NH 2 terminus) and EcoRI (COOH terminus) restriction sites, which appended Myc and (His) 6 tags to the COOH terminus of FBLN-3. Afterward, the tagged FBLN-3 cDNA was PCR amplified using oligonucleotides containing BglII (NH 2 terminus) and XhoI (COOH terminus) restriction sites and ligated into identical sites in pMSCV-IRES-GFP (7). All FBLN-3 cDNA constructs were sequenced on an Applied Biosystems 377A DNA sequencing machine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting PCR fragment was ligated into pcDNA3.1/Myc-His B vector (Invitrogen, Carlsbad, CA) at HindIII (NH 2 terminus) and EcoRI (COOH terminus) restriction sites, which appended Myc and (His) 6 tags to the COOH terminus of FBLN-3. Afterward, the tagged FBLN-3 cDNA was PCR amplified using oligonucleotides containing BglII (NH 2 terminus) and XhoI (COOH terminus) restriction sites and ligated into identical sites in pMSCV-IRES-GFP (7). All FBLN-3 cDNA constructs were sequenced on an Applied Biosystems 377A DNA sequencing machine.…”
Section: Methodsmentioning
confidence: 99%
“…A key component of physiologic tissue development and repair is angiogenesis (3), which when left unchecked can promote the pathogenicity of diabetic retinopathy, arthritis, macular degeneration, endometriosis, inflammation, and cancer (4)(5)(6). We independently identified FBLN-5 as a novel gene target of the tumor suppressor, transforming growth factor-h, and showed that (a) FBLN-5 regulates normal and cancer cell proliferation, migration, and invasion in a cell-and context-specific manner (7,8); (b) tumorigenesis down-regulates FBLN-5 expression in metastatic human tumors (7); and (c) FBLN-5 antagonizes vascular endothelial growth factor (VEGF) signaling in and angiogenic sprouting by endothelial cells in vitro (8). Thus, FBLN-5 may suppress tumor formation and progression in part by antagonizing angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (38) showed fbln-5 increased cell proliferation of HT1080 fibrosarcoma cells synergistically with TGB-␤1, and enhanced fibronectin-induced HT1080 migration and invasion). Fbln-5 has also been shown to bind integrins (␣V␤3, ␣V␤5, and ␣9␤1) in vitro and to mediate cell attachment in an RGD motif-dependent manner in endothelial cells (10,39).…”
Section: Suppression Of Smc Proliferation and Migration By Fbln-5mentioning
confidence: 99%
“…Fibulin-5 is a recently discovered TGFb-regulated gene, which has tumor suppressor activity. Fibulin-5 is an ECM protein that is believed to signal through interaction with integrins (Schiemann et al, 2002). CTGF is a secreted protein involved in angiogenesis, skeletogenesis, and wound healing.…”
Section: Tgfb Receptor Expression and Activity In Human Rccmentioning
confidence: 99%